Anatomia de escapos de Tillandsia L. (Bromeliaceae) dos Campos Gerais do Paraná, Brasil - Segecin, Simone; Scatena, Vera L. [UNESP] (Sociedade Botânica de São Paulo, 2004)
Estudou-se a anatomia dos escapos de Tillandsia crocata (E. Morren) Baker, T. gardneri Lindl., T. geminiflora Brongn., T. linearis Vell., T. lorentziana Griseb., T. mallemontii Glaziou ex Mez, T. recurvata L., T. streptocarpa Baker, T. stricta Soland ex Sims, T. tenuifolia L. e Tillandsia sp., que ocorrem nos Campos Gerais do Paraná. São plantas epífitas de galhos de árvores ou de paredões rochosos. Os escapos são eretos ou recurvados, revestidos por brácteas e emergem do centro da roseta foliar. Verificaram-se dois padrões anatômicos de distribuição dos feixes vasculares. Um padrão onde os feixes vasculares ocorrem condensados perifericamente no cilindro vascular, circundados e/ou imersos num cilindro esclerótico - periciclo. Outro padrão onde os feixes vasculares ocorrem dispersos, mas concentrados na periferia do cilindro vascular, envolvidos total ou parcialmente por bainha fibrosa, sem formar um cilindro esclerótico. A grande maioria das espécies apresenta escapos com epiderme de células espessadas, hipoderme com células espessadas, e feixes vasculares colaterais envolvidos total ou parcialmente por fibras. A presença de células com paredes espessadas, de hipoderme, de idioblastos de ráfides, mucilagem e canais de ar constituem características adaptativas ao hábito epifítico. Os tipos de espessamento das células epidérmicas, da hipoderme, e do periciclo, a distribuição dos feixes vasculares, e a presença de feixes vasculares compostos possibilitam separar as espécies dentro do gênero. É apresentada uma chave de identificação das Tillandsia estudadas com base nas características anatômicas do escapo.

The anatomy of Tillandsia crocata (E. Morren) Baker, T. gardneri Lindl., T. geminiflora Brongn., T. linearis Vell., T. lorentziana Griseb., T. mallemontii Glaziou ex Mez, T. recurvata L., T. streptocarpa Baker, T. stricta Soland ex Sims, T. tenuifolia L., and Tillandsia sp. scapes were studied. They occur in the Campos Gerais, state of Paraná, southern Brazil. They are epiphytics on trunks or rock slopes. Scapes are both bent or straight revested by bracts and they grow up from the center of the foliar rosette. There are two patterns of distribution concerning the vascular bundles, one of them the peripherical bundles are condensed in the vascular cilyndre surrounded and/or immersed in a sclerotic cilyndre, the pericycle. The other presents vascular bundles scattered but concentred on the vascular cylindre periphery, total or partially involved in a fibrous sheath without a sclerotic cylinder. Most of these species presents scapes with thickened wall hypodermic and epidermic cells, and colateral vascular bundles that are total ou partially involved by fibers. The presence of thickened wall cells, hypodermis, raphids idioblasts, mucilage and air channel are adaptatives characters related to the epiphytic habit. The kind of thickness of the epidermic cells, hypodermis and pericycle; the distribution of vascular bundles, and the presence of composite vascular bundles could help species delimitation into the genus. It is presented a identification key of Tillandsia to the anatomic features of the scape.
Anatomy of Tillandsia L. (Bromeliaceae) scapes from the Campos Gerais of Paraná, Brazil
Keywords: anatomia; Bromeliaceae; escapos; Tillandsia; anatomy; Bromeliaceae; scape; Tillandsia